Impact of the EU Economies’ Innovation Levels on The Flows of People at Their Labour Markets - Grażyna WĘGRZYN1; Marcin SALAMAGA2 (Communications of International Proceedings, 2021)
The study objective is to research the impact of an economy’s level of innovation on the structure of flows in the labour market. We conduct research for countries grouped by their level of innovation, i.e. Innovation Leaders, Strong Innovators, Moderate Innovators, and Emerging Innovators. The main contribution of the study is the identification of employee flow patterns in the labour markets of individual EU countries from the perspective of the levels of innovation of their respective economies. We demonstrate that the structure of flows in a labour market depends on the innovation level of the respective economy. Our analysis showed that in the countries classified as Moderate Innovators or Emerging Innovators, employees change jobs much less frequently than in those who enjoy a high level of innovation. In the Innovation Leader countries, employees smoothly move from one employer to another. Workforce flows between workplaces are a natural phenomenon. In countries who are Innovation Leaders, an increase in the participation in lifelong learning gives rise to a parallel increase in employee flow (EE) and job-to-job employee turnover. In countries who are Emerging Innovators, increasing the participation in lifelong learning increases the turnover mainly among young people (15-24 age group).
Keywords: Labour Market Flow; Transitions in Labour Market Status; Job-To-Job; Innovation Economy